ROLE OF BETA-ADRENOBLOCKERS IN ARTERIAL HYPERTENSION TREATMENT. WHAT DO EVIDENCE BASED MEDICINE DATA SHOW? - S. Y. Martsevich (Рациональная фармакотерапия в кардиологии, 2016)
The beta-blocker role in arterial hypertension treatment is surveyed from the positions of evidence based medicine and international clinical guidelines. Data of last randomized clinical trials and meta-analyses are discussed.